Adsorption Of The Pesticides Bentazon, Carbofuran And 2,4-Dichlorophenoxyacetic Acid By Mesoporous Activated Carbons Prepared From Agriculture Waste - Salman, Jassem Mohammed (2010)

(untitled)
The adsorption of bentazon, carbofuran and 2,4-dichlorophenoxyacetic acid (2,4-D) from aqueous solution by activated carbons prepared from agricultural waste materials (palm oil fronds, banana stalks and date stones) was studied using batch and continuous processes. Mesoporous activated carbons with high surface areas were prepared by physiochemical activation method consisting of potassium hydroxide (KOH) impregnation and carbon dioxide (CO2) gasification. Various parameters, such as activation temperature, activation time and chemical impregnation ratio (IR= wKOH /wchar), which have influence on the structure and performance of the activated carbons, were examined. The optimum conditions obtained for the prepared activated carbons using response surface methodology were 750 oC at 3 h and impregnation ratio of 3.75 for palm oil fronds activated carbon (PFAC), 740.5 oC at 1.08 h and impregnation ratio of 2.3 for banana stalk activated carbon (BSAC), and 850 oC at 2.97 h with impregnation ratio of 3.75 for date stone activated carbon (DSAC).